How Contracts Influence Trust and Distrust. (May 2017) - Lumineau, Fabrice
Despite the scholarly interest in contracts and trust governing interorganizational relationships, an understanding of how contracts influence trust remains limited by the way in which the interaction between the two constructs is conceptualized. By bringing together recent advances in the literature on interorganizational governance, I consider (a) the controlling and the coordinating dimensions of formal contracts, (b) trust and distrust as two distinct constructs, and (c) both the calculative and noncalculative aspects behind the development of trust and distrust. Drawing upon information-processing theory, I develop a series of propositions about how each contractual dimension influences the development of trust and distrust by inducing specific information-processing and decision-making mechanisms. My theoretical analysis leads me to discuss the trade-offs inherent in governance choices, and I discuss the implications of my propositions for the literature on interorganizational governance mechanisms.